PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP LOYALITAS KARYAWAN PADA PT. PERMODALAN EKONOMI RAKYAT PEKANBARU - Ashido, Yosiandri; ', Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This study aims to analyze the influence of organizational culture and work motivation on employee loyalty at PT. Permodalan Ekonomi Rakyat Pekanbaru. The method used is quantitative with a descriptive approach and multiple linear regression analysis, with data obtained from questionnaires distributed to 80 employees. The independent variables in this study are organizational culture (X1) and work motivation (X2), while the dependent variable is employee loyalty (Y). The results of the study indicate that organizational culture has a positive and significant effect on employee loyalty (t_count 2.565> t_table 1.990; significance 0.012 t_table 1.990; significance 0.000 F_table 3.12; significance 0.000